The Influence Of Problem Based Learning (PBL) On The Learning Motivation Of Class III Students At State Elementary School - Sihombing, Lisbet Novianti (Jurnal Ilmu Sosial Mamangan, 2025)
This study aims to determine the effect of Problem Based Learning (PBL) on the Learning Motivation of Class VII Students at SD 122379 Pematang Siantar for the 2023/2024 Academic Year. This type of research is quantitative research with quantitative descriptive data analysis approach. The research population is students. The research sample amounted to 64 people. The sampling technique used is purposive sampling technique. The data collection technique used is a questionnaire (questionnaire). The hypothesis testing technique uses simple linear regression analysis and the coefficient of determination (R2). The results of the study are that there is a significant influence between Problem Based Learning (PBL) on the Learning Motivation of Class VII Students at SD 122379 Pematang Siantar for the 2023/2024 Academic Year, which is a significant value of 0.000 <0.05. In this study, the table obtained the R Square value of 0.689. This means that the effect of the Problem Based Learning variable on students' learning motivation is 68.9%.